Influence of electric arc furnace dust and lime kiln waste in Portland cement hydration - Metz, Josué Claudio; Maciel, Elenize Ferreira; Garbin, Marilise; Modolo, Regina Célia Espinosa; Moraes, Carlos Alberto Mendes; Moraes, Carlos Alberto Mendes; Gomes, Lucas Bonn; Brehm, Feliciane Andrade (Ambiente Construído, 2020)
Studies have indicated that the use of electric arc furnace dust (EAFD) results in a delay in the hydration time of Portland cement. Calcium-rich waste such as lime kiln waste (LKW) is one of the techniques used to offset this delay as it accounts for the lack of this element in calcium silicate hydrate (C-S-H) production in the mixture. The objective of this study was to evaluate the influence of electric arc furnace dust (EAFD) and lime kiln waste (LKW) in the hydration process of Portland cement pastes and their influence in setting time and hydration heat. The methodology used required several steps: physiochemical and micro-structural characterization of waste samples; definition and production cement pastes with different levels of waste substitution and a reference paste and evaluation of the cement pastes with respect to setting time and hydration heat. Results showed that the substitution of 1% EAFD with or without LKW presented similar hydration heats as the reference paste. This indicated that EAFD+LKW substitution would not affect substantially the hydration reactions of cement and could allow waste recycling in construction materials.